Effect of Prophylactic Treatments on Demineralized Dental Enamel - Esteves Torres, Fernanda Ferrari (2024)
Although professional prophylaxis is beneficial in controlling dental biofilm, its effects on tooth surfaces with white spot lesions are still poorly understood. The objective of this study was to evaluate, in vitro, the effect of different methods used in dental prophylaxis on the mineral content of demineralized enamel surfaces, using quantitative light-induced fluorescence (QLF). Extracted sound premolars were used (n=40). The sample was made up of 4 groups: G1 - Robinson brush and pumice stone; G2 - Robinson brush and prophylactic paste; G3 - Rubber and pumice bowl; G4 - Rubber cup and prophylactic paste. The evaluations were carried out at 3 levels: with the tooth healthy, immediately after the demineralization process and after application of the proposed treatments. The primary variable analyzed was the mineral content of the enamel, quantified using QLF. The data did not meet the assumptions for parametric tests, so the Friedman variance test was applied using version 5.0 of the BioEstat program. The significance level adopted was 5%. In Group I, a statistically significant difference (p<0.001) was observed between the mineral content of the sound tooth and after demineralization, indicating a white spot formation, but no significant changes (p=0.082) post-treatment with a Robinson brush and pumice stone. Group II showed similar results. Group III exhibited significant changes (p<0.001) post-demineralization and improvement (p<0.001) with a rubber cup and pumice stone. Group IV also showed significant demineralization (p<0.001) and partial remineralization (p<0.001) with a rubber cup and prophylactic paste, indicating that these treatments can improve mineral content in demineralized enamel. In conclusion, treatments using a rubber cup with pumice stone or prophylactic paste resulted in partial remineralization of demineralized enamel, while treatments using a Robinson brush did not cause significant changes in mineral content.